TICK-BORNE RICKETTSIAE OF THE SPOTTED FEVER GROUP IN WEST PAKISTAN: I. ISOLATION OF STRAINS FROM TICKS IN DIFFERENT HABITATS - ROBERTSON, RICHARD G.; WISSEMAN, CHARLES L.; TRAUB, ROBERT (Oxford University Press, 1970)
Robertson, R. G., C. L. Wisseman, Jr. (Dept. Microbiology, Univ. of Maryland School of Medicine, Baltimore, Md. 21201) and R. Troub. Tick-borne rickettsiae of the spotted fever group in West Pakistan. I. Isolation of strains from ticks in different habitats. Amer. J. Epid., 1970, 92: 382–394.—Pools of ixodid ticks, collected from many mammalian species in a wide variety of habitats in West Pakistan, were examined for the presence of spotted fever group rickettsiae by inoculation into guinea pigs. Of 107 pools inoculated, representing a total of 2857 ticks, 53 pools yielded presumptive isolates, i.e., they caused the inoculated animals to develop complement-fixing antibodies for the spotted fever group of rickettsiae. Out of the 53 presumptive isolates, 13 confirmed isolates have already been established in the laboratory. Based on both the presumptive and confirmed isolates, it is concluded that: 1) a high proportion of ixodid tick pools of at least 6 genera in West Pakistan harbor spotted fever group rickettsiae, 2) infected ticks are widely distributed throughout West Pakistan in habitats ranging from semi-desert plains through alpine and arctic terrain in the Himalayan Mountain to the mountain deserts of Gilgit Agency.